DEVELOPMENT OF CREATIVE PERSONALITY OF PRIMARY SCHOOL STUDENT ON THE BASIS OF PERSONALLY ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2022)
In the article the value of the personality oriented method opens up of studies for forming f creative personality ond found out the levels of verbal and vivid creative thought of pupils of 2-5 forms.
Keywords: development of creative thought; personality oriemed shudies